IMPROVING THE QUALITY OF LIFE THROUGH EDUCATION IN THE COMMUNITY LEARNING ACTIVITY CENTER (PKBM) - Mira Azzasyofia (Politeknik Kesejahteraan Sosial Bandung, 2019)
This research discusses about how the existence of PKBM Paksi Safa Kawijayan in Cipinang Besar Utara Subdistrict and its relationship with efforts to improve the quality of life of the community living around PKBM Paksi Safa Kawijayaan. The purpose of this research is to provide an overview of the quality of life of the people who participate in the educational programs provided by PKBM Paksi Safa Kawijayaan. The research method used is a qualitative research with descriptive method. The results of this study indicate that the existence of PKBM Paksi Safa Kawijayan has improved the quality of life of the surrounding community, especially street children who are the targets of the Paksi Safa Kawijayan PKBM programs. This quality of life improvement can be seen in the economic, political, health, environmental and educational aspects.